Preoperative evaluation of pulmonary artery morphology and pulmonary circulation in neonates with pulmonary atresia - usefulness of MR angiography in clinical routine - Kawel Nadine; Valsangiacomo-Buechel Emanuela; Hoop Ricarda; Kellenberger Christian J (Journal of Cardiovascular Magnetic Resonance, 2010)
Abstract Background To explore the role of contrast-enhanced magnetic resonance angiography (CE-MRA) in clinical routine for evaluating neonates with pulmonary atresia (PA) and to describe their pulmonary artery morphology and blood supply. CE-MRA studies of 15 neonates with PA (12 female; median weight: 2900 g) were retrospectively evaluated by two radiologists in consensus. Each study was judged to be either diagnostic or non-diagnostic depending on the potential to evaluate pulmonary artery morphology and pulmonary blood supply. In those cases where surgery or conventional angiocardiography was performed results were compared. Results CE-MRA was considered diagnostic in 87%. Pulmonary artery morphology was classified as "confluent with (n = 1) and without (n = 1) main pulmonary artery", "non-confluent" (n = 6) or "absent" (n = 7). Source of pulmonary blood supply was "a persistent arterial duct" (n = 12), "a direct" (n = 22) or "indirect (n = 9) aortopulmonary collateral artery (APCA)" or "an APCA from the ascending aorta" (n = 2). In no patient were there any additional findings at surgery or conventional angiocardiography which would have changed the therapeutic or surgical approach. Conclusions CE-MRA is a useful diagnostic tool for the preoperative evaluation of the morphology of pulmonary arteries and blood supply in neonates with PA. In most cases diagnostic cardiac catheterization can be avoided.